2020
DOI: 10.1002/jlb.5covr0620-306r
|View full text |Cite
|
Sign up to set email alerts
|

BTK/ITK dual inhibitors: Modulating immunopathology and lymphopenia for COVID-19 therapy

Abstract: Bruton's tyrosine kinase (BTK) signaling is involved in innate immune responses and regulates the production of proinflammatory cytokines that can contribute to COVID-19 immunopathology. Clinical trials with BTK inhibitors in COVID-19 treatment have been proposed, and previous studies have attempted to investigate the therapeutic effects of ibrutinib and underlying mechanisms in treating viral pneumonia. These attempts, however, did not consider potential off target effect of BTK inhibitors on T cell different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The hence might be beneficial in treating COVID-19 related immunopathology and lymphopenia 53 . This has been already tested in clinical trials 54 and for dasatinib it has been confirmed from seminal studies in chronic myelogenous leukemia 55 inhibition of the viral replication mechanisms and c) where required, protective effects which account for other underlying conditions like cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The hence might be beneficial in treating COVID-19 related immunopathology and lymphopenia 53 . This has been already tested in clinical trials 54 and for dasatinib it has been confirmed from seminal studies in chronic myelogenous leukemia 55 inhibition of the viral replication mechanisms and c) where required, protective effects which account for other underlying conditions like cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NF-kB plays a key role in the pathogenesis of coronaviruses ( DeDiego et al, 2014 ; Kanzawa et al, 2006 ; Yang et al, 2017 ). It has been observed that tyrosine kinase activity is increased in COVID-19 ( McGee et al, 2020 ), which leads to phospholipase C (PLC) activation that actives protein kinase C (PKC). This induces reactive oxygen species (ROS) increase, ROS-mediated NF-kappa B (NF-kB) activation, and mTOR inhibition, which result in the transcriptional activation of NF-kB target genes.…”
Section: Mainmentioning
confidence: 99%
“…These patients display lymphopenia, stimulation and malfunction of lymphocytes, defects of granulocytes and monocytes, elevated levels of cytokines, and higher amounts of immunoglobulin G (IgG) and total antibodies [66] (Figure 8). Extreme and fatal COVID-19 is linked with lymphopenia and an elevated amount of blood neutrophils [67]. Lymphocyte counts of 800 cells/μl and a decreased probability of recovery are reported in ICU patients suffering from COVID-19.…”
Section: Immunopathology Of Sars-cov2mentioning
confidence: 99%